CHRONIC MUSCULOSKELETAL PAIN DIMINISHES THE MULTISCALE COMPLEXITY OF STANDING POSTURAL CONTROL IN OLDER ADULTS. (11th November 2018) - Cai, Y; Zhou, J; Manor, B; Lipsitz, L; Leveille, S
Abstract: Chronic musculoskeletal pain (CMP) contributes to increased fall risk among older adults. Fall often occurs due to loss of standing balance. Standing postural control is "complex", depending upon numerous inputs interacting across multiple temporal-spatial scales. The decreased complexity has been linked to increased fall risk. Pain may interfere with this metric of postural control, thus, lead to falls. The aim of this study is to determine whether CMP is associated with sway complexity in older adults. In the MOBILIZE Boston Study, 738 community-dwelling adults aged ≥70y completed a functional assessment, including eyes-open standing postural sway on a force plate. The degree of sway complexity was quantified using multiscale entropy. The Brief Pain Inventory and McGill Pain Map assessed global pain severity and pain locations, respectively. Relationships between pain and sway complexity were analyzed using multivariable Generalized Linear Models. More severe pain was significantly associated with peripheral neuropathy, impaired processing speed (Trail Making A (TMT-A)) and global cognitive function (Mini-Mental State Examination (MMSE). Those with moderate-to-severe pain had lower complexity compared to those with mild or no pain (p=0.01), adjusted for age, gender, education, neuropathy, and TMT-A or MMSE. Participants with lower leg pain had lower sway complexity than those without (p=0.01); no association between pain in other body sites and sway complexity were observed. CMP severity and lower leg pain are associated with decreased sway complexity in older adults. Future studies are needed to explore the underlying mechanisms through which the CMP affects sway complexity, thus, contributes to falls.